Targeting memory reconsolidation to prevent the return of fear in patients with fear of flying. Issue 7 (5th April 2017) - Maples‐Keller, Jessica L.; Price, Matthew; Jovanovic, Tanja; Norrholm, Seth D.; Odenat, Lydia; Post, Loren; Zwiebach, Liza; Breazeale, Kathryn; Gross, Robin; Kim, Sae‐Jin; Rothbaum, Barbara Olasov
Abstract : Background: When a memory is recalled, it may again exist in a labile state and stored information becomes amenable to change, a psychobiological process known as reconsolidation. Exposure therapy for anxiety disorders involves accessing a fear memory and modifying it with less fearful information. A preclinical study reported that providing a reminder of a fear memory 10 min prior to extinction training in humans decreased fear up to 1 year later (Schiller et al., 2010). Methods: For this pilot clinical study, we used virtual reality exposure therapy (VRE) for fear of flying (FoF) to determine if using a cue to reactivate the memory of the feared stimulus 10 min prior to exposure sessions leads to fewer anxiety‐related behaviors and a more durable response compared to a neutral cue. FoF participants ( N = 89) received four sessions of anxiety management training followed by four sessions of VRE. Participants were randomly assigned to receive an FoF cue (reactivation group) or a neutral cue (control group) prior to the VRE sessions. Heart rate (HR) and skin conductance levels (SCLs) were collected during posttreatment and 3‐month follow‐up assessments as objective markers of fear responding. Results: Treatment was effective and all clinical measures improved equally between groups at posttreatment with maintained gains through follow‐ups. Significant differences were identified with regard to HR and SCL indices. Conclusions: These results suggest that memory reactivation prior to exposure therapy did not have an impact on clinical measures but may enhance the effect of exposure therapy at the physiological level.